A Scott-Type Regression Test of the Dividend Ratio Model - Shiller, Robert J. (The Review of Economics and Statistics, 1990)
Tests of a representation of the efficient markets model (the dividend-rtaio model of Campbell and Shiller (1988a)) of the stock market can be made by regressing (transformed) ex-post values on (transformed) actual values and testing whether the slope coefficient is one. Such tests are run here with some improvements. The results of the tests are that the efficient markets model is strongly rejected with U.S. data 1901-1987 in favor of an alternative that stock prices should have been much less volatile. Copyright 1990 by MIT Press.